2014
DOI: 10.1016/j.ijsu.2014.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cholecystectomy during gastric and oesophageal resection: A retrospective analysis and critical review of literature

Abstract: The higher incidence of gallstone formation after gastrectomy for cancer has been reported as a common complication in many studies but the management strategies are still controversial and need further evaluation. We retrospectivaly analysed between 2007 and 2013, 206 patients who underwent gastric and or oesophageal resection. In 29/93 patients receiving an oesophagectomy a simultaneous cholecystectomy was performed, respectively 31 from 111 patients who underwent a gastrectomy received an incidental cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…Although several studies confirmed that the incidence of gallstones after gastrectomy is significantly higher than that in patients without upper gastrointestinal surgery, whether there is a need for preventive gallbladder resection in gastric cancer surgery remains controversial. The incidence of gallstones and symptomatic cholelithiasis requiring cholecystectomy after gastric cancer surgery is still relatively low [9]. In the present study, we observed cholecystolithiasis after gastrectomy in only 8.98% of patients, which was lower than the rates of 13–22% reported in previous studies [2, 4, 6].…”
Section: Discussioncontrasting
confidence: 81%
“…Although several studies confirmed that the incidence of gallstones after gastrectomy is significantly higher than that in patients without upper gastrointestinal surgery, whether there is a need for preventive gallbladder resection in gastric cancer surgery remains controversial. The incidence of gallstones and symptomatic cholelithiasis requiring cholecystectomy after gastric cancer surgery is still relatively low [9]. In the present study, we observed cholecystolithiasis after gastrectomy in only 8.98% of patients, which was lower than the rates of 13–22% reported in previous studies [2, 4, 6].…”
Section: Discussioncontrasting
confidence: 81%
“…The reason for prophylactic cholecystectomy is the incidence of gallstones after gastrectomy was considerably higher than was the prevalence of gallstones detected during the health examination in Korea (2.3–4.9%). 25 26 The main pathophysiologic mechanism is considered to be an interruption of the anterior hepatic branch of the vagus nerve—a condition which leads to bile juice stagnation. So, is prophylactic cholecystectomy needed?…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above evidence, we summarized the mechanism as shown in Figure 1 . We believe that injury or resection of the vagus nerve or changes in intestinal hormone secretion can lead to physiological dysfunction of the gallbladder ( 23 ) and Oddi sphincter, and the lithogenic components in the bile are also changed, ultimately leading to CL ( 12 , 14 , 16 , 18 , 20 , 24 ).…”
Section: Causes and Mechanism Of CL Development After Gc Surgerymentioning
confidence: 99%